Peran Ganda Istri Dalam Keluarga (Studi Kasus Istri Petani di Desa Jombang Kecamatan Jombang) - Khurin In'Ratnasari; Akhmad Zaeni (Mabahits : Jurnal Hukum Keluarga Islam, 2020)
The purpose of this paper is to identify the dual role of women in the era of globalization, this study uses descriptive qualitative methods, the findings of this discussion are that women play a major role as domestic workers, but over time there has been a shift from the beginning. domestic shifts to the public, some of the reasons for women to work in the public sector in relation to economic (economic) values ​​in the family, as well as to utilize their function as fully human without discrimination for women Keywords: Women, Multiple Roles, Family